Risk of Lymphoma and Solid Cancer among Patients with Rheumatoid Arthritis in a Primary Care Setting - Andersen, Christen Lykkegaard (Public Library of Science, 2014)
BACKGROUND: Several studies have demonstrated an association between rheumatoid arthritis (RA) and lymphoproliferative malignancies, but pathogenic mechanisms remain unclear. We investigated 1) the risk of lymphoproliferative malignancies and solid tumors in adults with RA identified in primary care and 2) the possible mediating role of blood eosinophilia in the clonal evolution of cancer in these patients. METHODS: From the Copenhagen Primary Care Differential Count (CopDiff) Database, we identified 356,196 individuals with at least one differential cell count (DIFF) encompassing the eosinophil count between 2000–2007. From these, one DIFF was randomly chosen (the index DIFF). By linking to the Danish National Patient Register, we categorized the selected individuals according to known longstanding (≥3 years) or recent onset (<3 years) RA prior to the index DIFF. In addition, the cohort was stratified according to management in primary or secondary care. From the Danish Cancer Registry we ascertained malignancies within four years following the index DIFF. Using multivariable logistic regression, odds ratios (OR) were calculated and adjusted for sex, age, year, month, eosinophilia, comorbid conditions and C-reactive protein (CRP). RESULTS: 921 patients had recent onset RA and 2,578 had longer disease duration. Seventy three percent of RA patients were managed in primary care. After adjustment for sex, age, year, and month, neither recent onset nor long-standing RA was associated with incident lymphoproliferative malignancies or solid cancers. These risk estimates did not change when eosinophilia, CRP, and comorbidities were included in the models. CONCLUSIONS: In this large cohort of patients with RA of short or long duration recruited from a primary care resource, RA was not associated with an increased risk of lymphoproliferative or solid cancers during 4 years of follow-up, when the models were adjusted for confounders. Blood eosinophilia could not be identified as a mediator of cancer development in the present setting.